Freakery and Prosthetic Actuality in Joseph Chaikin's Body Pieces - Telory W. Davies (Disability Studies Quarterly, 2005)
Whereas his early exploration of disability issues addressed impairment as a point of departure for non-standard theater, Joseph Chaikin's Body Pieces in 2001 made disability the standard frame of reference. In this workshop production, amputee characters and actors mitigated audience alienation and fear of dismemberment by attaching and detaching their prosthetic limbs both on and off the stage. Chaikin combined humor with actuality in these moments, inviting spectators to contemplate their relation to disability. In his post-stroke aphasic direction of this piece, Chaikin necessitated a similar reconception of mental wholeness. His disabled actors provided a physical model for reassessing ability where cognitive and physical fragmentation replaced wholeness as new actualities: they exposed and detached their prosthetic legs in order to revise audience perceptions of fragmented bodies. Chaikin and his actors used comedy to familiarize the unfamiliarity of amputee bodies and to critique non-disabled responses to disabled difference. Appropriating the traditional freak show premise, Chaikin and disabled playwright John Belluso forged a contemporary meditation on freakery that played with and against sideshow stereotypes.
Keywords: Amputees and performance; Joseph Chaikin; disability and comedy